Ratio Legis of Chemical Castration to the Perpetrators of Sexual Violence against Children - Henny Yuningsih (Faculty of Law, Sriwijaya University, Indonesia, 2020)
The government responds to the increasing number of cases of sexual crimes against children by legalizing Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection. This regulation emphasises on increasing the severity of criminal sanctions and the imposition of an additional penalty for perpetrators of sexual violence against children. It is effective to give deterrent effects, to prevent future crimes, and to provide rehabilitation. Furthermore, Government Regulation in Lieu of Law No. 1 of 2016 has been amended into Law No. 17 of 2016 concerning Stipulation of Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection into Law. The juridical foundation will be used as a legal basis for the new law, namely the Draft Bill concerning amendments to Law No. 23 of 2002 concerning Child Protection. Cases of sexual violence against children are increasing, threatening children's strategic role as the nation's future. Hence, the state needs to increase the severity of criminal sanctions and to take action against perpetrators of sexual violence against children